Bridging the financial literacy gender gap in Uganda: Insights for educators and Librarians - Namawejje, Hellen; Yawe, Bruno L. (Informa UK Limited, 2025)
This study examines gender disparities in financial literacy among students in Business, Technical, and Vocational Education and Training (BTVET) institutions in Uganda. Data was collected through structured questionnaires from 400 BTVET students in the central region of Uganda, selected via stratified random sampling. The study’s objectives are to evaluate financial literacy levels by gender and identify factors influencing these levels. Analytical methods include descriptive statistics, t-tests, and Ordinary Least Squares (OLS) regression. Results indicate that male students generally have higher financial literacy levels than female students. Specifically, male students significantly outperform female students in technical fields, while female students show greater financial literacy in education fields compared to their male counterparts. The study identifies age and financial confidence as key determinants of financial literacy for both genders. Additionally, while parents’ education plays a significant role in enhancing financial literacy among male students, female students’ financial literacy is more influenced by their financial management skills and parental discussions on savings and spending. The study highlights the need for targeted initiatives to promote gender equality in technical education. Such initiatives could include mentorship programs, scholarships, library partnerships, and awareness campaigns aimed at encouraging female students to pursue technical fields and providing them with the necessary support to excel. These measures are essential for closing the financial literacy gender gap among BTVET students in Uganda.